Synthesis of mesogen-nanoparticle composites by doping 4-decyloxybenzoic acid with substrate-functionalized ZnO nanoparticle - Paul, Saurav; Chakraborty, Bimal Bhushan; Deb, Kuheli; Choudhury, Sudip (Komunitas Ilmuwan dan Profesional Muslim Indonesia, 2023)
Nanomaterials and Mesogenic materials are two important pillars of today’s science and technology, in the fields of both material and biological applications. Mesogens or liquid crystals (LC) are self-aggregated anisotropic fluids with long range order, and the nature of self-aggregation largely controls their physical and material properties. Doping of nanomaterials over liquid crystalline matrix can provide valuable tools for development of materials with new or improved properties. In the present work 4-decyloxybenzoic acid is taken as the mesogenic matrix. It is observed that, composite prepared by doping of 4-decyloxybenzoic acid mesogen matrix by ZnO nanoparticle pre-functionalized with the same mesogen, caused a marked alteration in the mesogenic behavior. With 3% doping of matrix pre-functionalized ZnO NP on 4- decyloxy benzoic acid, we could achieve a shift of about 31ºC in the N-Iso transition temperature and, a decrease of >10ºC for the onset of liquid crystallinity by this method without quenching any of the mesophases exhibited by the pure mesogen. The synthesized materials have been characterized by variable temperature Polarised optical microscopy (POM), DSC, FTIR, XRD, EDX, and TEM This process may be considered for preparation other nanoparticle-mesogen composites as well. It was observed that, the effect of doping on the transition temperature and enthalpy of 4-Decyloxybenzoic Acid can be significantly enhanced by pre-functionalizing the dopant (ZnO NP) with the substrate molecules and then mixing this substrate functionalized ZnO nanoparticle with the bulk substrate.